Estudo das interações de Van der Waals no contexto da Teoria do Funcional da densidade e aplicações em nanoestruturas - Matheus Josue de Souza Matos (2009)
The dispersion term in van der Waals interaction is a manifestation of electronic correlation energy, and it is fundamental in the description of several physical systems. In spite of the exact solution of Density Functional Theory contains all description of this kind of interaction the implementation of the theory with approximations for the exchange correlation functional brings difficulties for the correct treatment of these interactions. In this work, we investigate methodological developments which aim to overcome this limitation. In the first one, we implementeda semiempirical potential for the London dispersion term which was incorporated as a correction in the Kohn-Sham energy. As for the second, we studied the construction of an exchange correlation functional for the first-principles treatment of van der Waals interaction. Both caseswere tested with applications in systems formed by nanostructures interacting among themselves or with other molecules by means of this kind of interaction. As examples, we cite the adsorption of benzene and oxygen in carbon nanotubes, the deposition of nanotubes on top ofarrays of silanes molecules, the adsorption of biological molecule, adenine, in graphene, and the interaction of graphene sheets with nanotubes and fullerenes.